Metodologi Studi Islam dalam Menyikapi Kontradiksi Hadis (Mukhtalaf al-Hadits) - Syaripudin, Ahmad (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2018)
The Method of Islamic Studies in addressing the contradictions in the Hadith (Mukhtalaf Al-HadÄ«á¹¡). This article is aimed to explain The Method of Islamic Studies in addressing the contradictions in the Hadith (Mukhtalaf Al-HadÄ«á¹¡) by citing an example of a Hadith is considered contradictory, and the role of the ulama in explaining the Mukhtalaf Al-HadÄ«á¹¡.